Design and simulation of Orthogonal Frequency Division Multiplexing transceiver system using Differential Phase Shift Keying (DPSK) for Wireless Local Area Network - Hasliza, A. Rahim; Murthy, N. S.; Mohd Fareq, Abd Malek. Dr.; R. Badlishah, Ahmad, Assoc. Prof. Dr.; 'Aini Syuhada, Md Zain (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/